PERBEDAAN MOTIVASI BELAJAR MAHASISWA INDEKOS DENGAN MAHASISWA YANG TINGGAL BERSAMA ORANG TUA - Santia Lestari; Siti Fatimah; Edutivia Mardetini (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2022)
The purpose of this studty was to show the difference in learning motivation between indekos and students who live with their parent. This research is comparative research using quantitative methods. The Product Moment Correlation formula is used for instrument validation and the Spearman Brown formula (Split Half Method) is used for reliability testing. The population of this study is all students of Economic Education 2018 Faculty of Teacher Training and Education, Sriwijaya University, which amounts to 62 people. Questionnaires and interviews are used for variable data X1 (motivation to study indekos students) and X2 (motivation to learn students who live with their parents). The results of this study showed that there was no significant difference between the learning motivations of indekos students and students who lived with parents. The motivation to study indekos students has an average of (80.71), while the motivation to learn students who live with parents is (84). The hypothesis using parametric statistics the t-test is obtained that thitung=-8.09 ≤ ttabel =1.671 then Ha was rejected and Ho accepted.